Comparison of [d-ala6-pro9net]-lhrh and [d-leu6-pro9net]-lhrh - effects on blood plasma gth-ii levels in captive striped bass - Blacio Game, Jorge Enrique (1997)
Comparison of [D-Ala6-Pro9NET]-LHRH and [D-Leu6-Pro9NET]-LHRH - EFFECTS ON BLOOD PLASMA GtH-II LEVELS IN CAPTIVE STRIPED BASS